استراتيجية الحملات الإعلامية في الجزائر وأسلوب اتخاذ القرار: مهنٌ جديدةٌ للاتصال في عالمٍ متحوّل - بوزانة, رفيق (جامعة الوادي - University of Eloued, 2022)
سنحاول في هذه الورقة البحثية تقديم مجموعة من الإجابات على مجموعة من التساؤلات التي ستشكل في المحصلة أدوات علميّة تُساعد المختص في الاتصال على وضع برنامج اتصالي يمكّنه من معالجة المشكلات الاتصالية التي تعانيها المؤسسة أو المشكلات الاتصالية التي يمكن أن تطرح في المجتمع، خاصة مع ما عاشه العالم عموماً والجزائر على وجه التحديد من أزمات بعد انتشار جائحة كورونا جعلت كل المسؤولين في كل المواقع والقطاعات يبدون اهتماماً أكبر للنشاطات الاتصالية التوعوية للحد من انتشار الجائحة. وتُشكّل هذه الإجابات منطلقات للتفكير في تطوير ممارسات ومهن الاتصال في الجزائر ما يفتح آفاقاً جديدة للتشغيل في هذا القطاع الاقتصادي الجالب للثروة. In this research paper, we will try to give answers to many questions that will eventually form scientific tools that will help the communication specialist to develop a communication program that enables him to resolve the communication problems that may arise in society, especially with crises that the world has experienced, in particular after the spread of the Corona pandemic, which made all officials in sectors show greater interest in awareness-raising using communication activities to limit the spread of the pandemic. These answers constitute starting points for thinking about the development of communication professions in Algeria, which opens new horizons for employment in this wealth-producing economic sector.
The media campaigns strategy in Algeria and the method of decision-making New professions for communication in a changing world
مقال
Keywords: استراتيجية الاتصال ، مهن الاتصال، الحملات الإعلامية ، القطاع الاقتصادي للإعلان; Communication strategy, communication professions, media campaigns, the economic sector of advertising.